Tungsten exposure causes a selective loss of histone demethylase protein. Issue 7 (30th March 2017) - Laulicht‐Glick, Freda; Wu, Feng; Zhang, Xiaoru; Jordan, Ashley; Brocato, Jason; Kluz, Thomas; Sun, Hong; Costa, Max
Abstract : In the course of our investigations into the toxicity of tungstate, we discovered that cellular exposure resulted in the loss of the histone demethylase protein. We specifically investigated the loss of two histone demethylase dioxygenases, JARID1A and JMJD1A. Both of these proteins were degraded in the presence of tungstate and this resulted in increased global levels of H3K4me3 and H3K9me2, the substrates of JARID1A and JMJD1A, respectively. Treatment with MG132 completely inhibited the loss of the demethylase proteins induced by tungstate treatment, suggesting that tungstate activated the proteasomal degradation of these proteins. The changes in global histone marks and loss of histone demethylase protein persisted for at least 48 h after removing sodium tungstate from the culture. The increase in global histone methylation remained when cells were cultured in methionine‐free media, indicating that the increased histone methylation did not depend upon any de novo methylation process, but rather was due to the loss of the demethylase protein. Similar increases of H3K4me3 and H3K9me2 were observed in the livers of the mice that were acutely exposed to tungstate via their drinking water. Taken together, our results indicated that tungstate exposure specifically reduced histone demethylase JARID1A and JMJD1A via proteasomal degradation, leading to increased histone methylation.